Cardiac Rehabilitation on Health Behaviors and Clinical Outcomes Among Myocardial Infarction Patients - Yusshy Kurnia Herliani; Yaowarat Matchim; Charuwan Kritpracha (International Journal of Public Health Science (IJPHS), 2016)
The lack of adherence to health behaviors in cardiac rehabilitation (CR) is the leading cause of recurrent myocardial infarction (MI) in Indonesia. This randomized control trial (RCT) study was conducted to examine the effect of a family based self-efficacy enhancing cardiac rehabilitation program on self-efficacy in cardiac health behaviors, health behaviors, and clinical outcomes among MI patients in Indonesia. Sixty MI patients who met the inclusion criteria were randomized by the modified stratified-block method and assigned into either the control group or the experimental group. The patients in the experimental group received the program during phase I over two days and continued to phase II of CR with weekly follow-up sessions. Patients were asked to complete the Self-Efficacy in Cardiac Health Behaviors Scale (SECHBS) and the Modified Myocardial Infarction Health Behaviors Questionnaire (Modified MIHBQ). The results revealed that self-efficacy, health behaviors, and clinical outcomes such as fasting blood glucose, total cholesterol, LDL, triglyceride, and BMI of the patients after receiving the intervention were significantly better than before receiving the intervention, except for blood pressure, and HDL levels. Self-efficacy, health behaviors, and clinical outcomes such as total cholesterol, LDL, and triglyceride were significantly better in patients in the experimental group than those in the control group (p < .05), except for blood pressure, HDL, BMI, and blood glucose levels (p > .05). In conclusion, the family based self-efficacy enhancing cardiac rehabilitation program shows evidence of effectiveness in enhancing self-efficacy, health behaviors, and some clinical outcomes in MI patients.